Study on Indium Free Transparent and Flexible Electrode: Dielectric/Metal/Dielectric Multilayer Structures from Smart Window to Semi-transparent Solar Cells - Bernède, J. C.; Cattin, L. (New Approaches in Engineering Research Vol. 10, 2021)
The present chapter is dedicated to In free transparent conductive and flexible multilayer electrodes. The new electrodes correspond to dielectric/metal/dielectric (D/M/D) multilayer structures deposited under vacuum. In the present work, after a fast review of the general properties of D/M/D electrodes using Ag as metal, we then develop the study of D/Cu/D multilayer structures. We propose to substitute Cu to Ag, because it is far cheaper. However, Cu having tendency to diffuse into many dielectrics it is difficult to obtain stable electrodes. We show that using Cu:alloys, i.e. Cu:Ni, Cu:Al and Cu:Ag, as metal it is possible to decrease significantly the Cu ions diffusion and to increase significantly the stability of the multilayer electrodes with Cu. Then, we show that when these electrodes are used as anode in organic photovoltaic cells, they can allow achieving efficiency similar to that obtained with ITO. Finally, we show that semi-transparent organic solar cells, with significant performances, can be obtained using D/M/D structures as top electrodes.